The effect of entrepreneurial orientation and dynamic capability on business performance in creative industry: Mediating role of innovativeness product advantage - Hikmah; Andalan Tri Ratnawati; Susetyo Darmanto (Global Business & Finance Review (GBFR), 2023)
Purpose: This study aims to analyze the effect of entrepreneurial orientation and dynamic capabilities on the innovativeness product advantage, the influence of entrepreneurial orientation and dynamic capabilities on the business performance of the creative industry, and the effect of innovativeness product advantage on the business performance of creative industries. This study also examines the mediating role of innovativeness product advantage in mediating entrepreneurial orientation and dynamic capabilities on creative industry business performance. Design/methodology/approach: The population is creative industry entrepreneurs in the Semarang city. Sample selection was done by purposive sampling method, obtained 150 data were declared eligible for analysis. Data analysis using SEM with IBM SPSS Amos 26.0,0 software tools. Findings: The research result showed that the entrepreneurial orientation and dynamic capability have a significant effect on the innovative product advantage and business performance. Another finding indicated that the innovative- ness product advantage had an mediating role on the influence of entrepreneurial orientation and dynamic capability toward business performance. Research limitation/implications: Despite following scientific principles, the sample limitation is a limitation of this research. Therefore, further research is expected to expand the scope of the research object to obtain more comprehensive results. To generalize the results, future research should include other antecedents, such as intellectual capital and networking. Originality/value: This research contributes to the development of resource-based theory by providing a better understanding of creative business development models. Furthermore, this research proposes the innovativeness product advantage so that the creative industry can compete in the digital era.
Keywords: 650; Creative industry; Entrepreneurial orientation; Dynamic capability; Innovativeness product advantage; Business performance